Adolescent BMI at Northern Israel: From Trends, to Associated Variables and Comorbidities, and to Medical Signatures. Issue 12 (March 2016) - Machluf, Yossy; Fink, Daniel; Farkash, Rivka; Rotkopf, Ron; Pirogovsky, Avinoam; Tal, Orna; Shohat, Tamar; Weisz, Giora; Ringler, Erez; Dagan, David; Chaiter, Yoram
Abstract : Abstract: The increasing prevalence of abnormal body mass index (BMI), mainly obesity, is becoming a significant public health problem. This cross-sectional study aimed to provide a comprehensive view of secular trends of BMI, and the associated socio-demographic variables and comorbidities among adolescents with abnormal BMI. Individuals of the study population were born mainly between 1970 and 1993, and were examined at 16 to 19 years of age during the years 1987 to 2010, at 1 conscription center in the northern district of Israel. The study population included 113, 694 adolescents. Univariate and multivariable logistic regression models were used to investigate the associations between BMI categories, socio-demographic variables, and medical conditions. A downward trend in the prevalence of normal BMI among both male and female adolescents was obtained, while trends of overweight and obesity (in both genders) and underweight (only among females) rose. Socio-demographic variables such as religion, education, family-related parameters, residential environment, country of birth, and origin were all associated with different risks for abnormal BMI. Obesity was associated with higher risk for hyperlipidemia, endocrine disorders (only in males), knee disorders, and hypertension type I + II (in both genders). Overweight was associated with knee disorders (only in females). Underweight, exclusively in males, was associated with increased risk for endocrine disorders, proteinuria, and cardiac disorders. Hierarchical clustering analysis revealed the intricate relations between gender, BMI, and medical signatures. It brought to light novel clusters of diseases that were abundant among populations having above-normal BMI or underweight males. Furthermore, above-normal BMI was associated with a lower rate of cardiac anomalies and scoliosis/kyphosis, whereas being underweight was associated with a lower risk for hypertension and flat foot. This study provides a reliable and in-depth view of secular trends in height, weight, and BMI of male and female adolescents. It supports previous associations between abnormal BMI and demographic variables and comorbidities, while uncovering novel associations, mainly regarding medical signatures of each gender–BMI group. This might lead to better monitoring, early detection, prevention, and treatment of various conditions associated to abnormal BMI categories and gender groups. Abstract : Supplemental Digital Content is available in the text